Labor patterns in Chinese women in Fuzhou attempting vaginal birth after previous cesarean delivery: a retrospective cohort study. Issue 12 (December 2019) - Zheng, Lianghui; Zhang, Qinjian; Liao, Qiuping; Chen, Rongxin; Xu, Rongli; Han, Qing; Yan, Jianying
Objective: To investigate the characteristics of labor in Chinese women who successfully have vaginal birth after cesarean section (VBAC). Methods: A retrospective cohort study was conducted in a hospital with 1000 beds between January 1 2015 and December 31 2017. A total 657 parturients with VBAC were selected. Women were divided into two groups according to previous cesarean section with or without trial of labor. Labor curves were analyzed and interval-censored regression was used to estimate the duration of labor. Results: The 95th percentile for the first stage of labor in VBAC was 13.03 hours, and labor accelerated after 4 cm of cervical dilation in both groups. The dilation rate in the trial of labor group was superior to that in the non-trial of labor group at 6–10 cm of dilation. After 6 cm, labor accelerated much faster in the trial of labor group than in the non-trial of labor group. Conclusions: Management of labor in parturients with VBAC whose cervical dilation is >6 cm should be treated differently according to previous cesarean section with or without trial of labor. If there is trial of labor in a previous delivery, the duration of labor should be shortened.